COURTSHIP: DATING IN TOXIC CONTROLLING AND DETRIMENTAL MENTAL HEALTH - Enjelia Enjelia; Lela Oktaria, Ryan Fernando, Maria Veronica (CV. Adiba Aisha Amira, 2024)
This research aims to determine the forms of toxic relationships in dating, the factors that cause toxic relationships in dating and the impact of toxic relationships on students who are victims of toxic relationships in reconnecting with the opposite sex. This activity uses interview and question and answer methods with the aim of exploring and studying the experiences of students who have been in toxic relationships while dating. The results of this activity for students who have experienced toxic relationships in dating show that first, the factors that cause toxic relationships in students are internal factors such as unstable emotional states, immature ways of thinking and victims of dependence on their partners, while. external factors such as the influence of the social environment, jealousy, cheating and disobedience. Second, the impact experienced by students who have experienced toxic relationships in dating When reconnecting with the opposite sex, there are psychological impacts such as the emergence of fear and trauma from reconnecting with the opposite sex. However, during the question and answer session, there was information that admitted that he had difficulty getting to know new people and ultimately chose to return to his toxic past on the grounds that his past loved him more than new people.